Perfectionism vis-à-vis Dance Motivation of Students in Learning the Art form in Selected Local Colleges in Pampanga, Philippines - Joseph Lobo; Genesis Dimalanta; Clarenz Bautista (Integrated Journal for Research in Arts and Humanities, 2022)
A descriptive-correlational study which aims to determine the relationship between perfectionism and dance motivation of students learning the art form from selected local colleges in Pampanga, Philippines. DMQ and BTPS were used to gather data from (378) Bachelor of Physical Education (BPEd) and Bachelor of Performing Arts (BPeA) students. Pearson r analysis result found out that perfectionism has a positive significant relationship to dance motivation of students. Based on the result, this study concludes that perfectionism has a positive outcome to students’ dance motivation in learning the said art form. This study provides new and valuable insight into perfectionism and dance motivation, most specifically in dance research. Limitations of this study is acknowledged and directions for future research is recommended.